Visual Aesthetic Expression On User-Generated Content By The Net Generation (Existence, Roles, And Opportunities In Cyberspace) - Amin, Hasanah Md. (The Turkish Online Journal of Design Art and Communication, 2012)
The overload content on Internet, has a direct connection with cyberspace particularly UGC. The space, the content, the creator, and the user are the complete component of cyberspace. The existence of cyberspace and its growing contents is real and overwhelming, where the creator roles is becoming demanding, and user opportunities are growing high. Visual as one of the properties of cyber contents is increasingly becoming more significant and popular amongst creator and user. Visual with aesthetic power could impress, influence, and favor biasness amongst the user. The content creator who knows how to manipulate this visuals and aesthetic expression can dominate the scenario and user who is ‘expressive literate’ will gain much from the scenes. User who understands visual aesthetic will be rewarded with competence, confidence, and certainly, a personality enhanced experience in carrying task when participating in this chaotic but promising cyber world. This article with the support of public-opinion polls and discussion forums explains the complete component of cyberspace, revealing some possible cognitive meanings, and emotional values behind it existence, it roles, and the opportunities offered by visual aesthetic.This is a space of opportunities where the ideal is - not ‘what you want’, but ‘how you want it to benefits you’.
Keywords: Aesthetic expression; Net generation; User-generated content; estetik ifade; net nesil; Kullanıcı tarafından oluşturulan içerik